2020
DOI: 10.2147/oaem.s229479
|View full text |Cite
|
Sign up to set email alerts
|

<p>Gait Speed at Discharge and Risk for Readmission or Death: A Prospective Study of an Emergency Ward Population</p>

Abstract: Background: There has been a growing interest in measuring gait speed for assessing longterm mortality and risk for hospital readmission in different populations. Objective: We studied the association between a 10-meter gait speed test at hospital discharge and the risk for 30-and 90-day hospital readmission or death in a mixed population of patients hospitalized for emergency care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…In addition, each 0.1 m/s lower gait speed was associated with a 10% higher odd of unplanned readmissions (OR 1.05 [ 95% CI 1.02 to 1.36]) and the odds for readmission were 3.95 times higher in the quartile with the slowest walkers compared to the fastest walkers (4.15 OR [ 95% CI 1.25 to 5.90]). These results are similar to those in the work of Hertzberg et al (2020) who found that for each 0.1 m/s decrease in 10MWT the ratio for 30-day readmission was 1.13 in the emergency ward population. Therefore, gait speed obtained through 10MWT seems to indicate physical impairment and, along with other risk factors, a helpful variable to determine the risk of early readmission in critical care survivors (Hertezerberg, 2020;Kon et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, each 0.1 m/s lower gait speed was associated with a 10% higher odd of unplanned readmissions (OR 1.05 [ 95% CI 1.02 to 1.36]) and the odds for readmission were 3.95 times higher in the quartile with the slowest walkers compared to the fastest walkers (4.15 OR [ 95% CI 1.25 to 5.90]). These results are similar to those in the work of Hertzberg et al (2020) who found that for each 0.1 m/s decrease in 10MWT the ratio for 30-day readmission was 1.13 in the emergency ward population. Therefore, gait speed obtained through 10MWT seems to indicate physical impairment and, along with other risk factors, a helpful variable to determine the risk of early readmission in critical care survivors (Hertezerberg, 2020;Kon et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…(2020) who found that for each 0.1 m/s decrease in 10MWT the ratio for 30‐day readmission was 1.13 in the emergency ward population. Therefore, gait speed obtained through 10MWT seems to indicate physical impairment and, along with other risk factors, a helpful variable to determine the risk of early readmission in critical care survivors (Hertezerberg, 2020; Kon et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Decreased walking speed has been proposed to be a surrogate marker of frailty and is associated with mortality, hospitalization, and nursing home disposition [51]. Further, some previous studies reported that low gait speed at discharge was associated with an increased risk of readmission [51,52]. It is hypothesized that gait impairment may represent a composite of other risk factors such as age, comorbidities, poor cardiopulmonary function, decrease in muscle strength or mass [53], falls [54], and the other characteristics that may be related to the risk of early readmission.…”
Section: Cga and Readmissionmentioning
confidence: 99%
“…It is particularly important that the mean age of the examined patients was 60.56 ± 5.11 years. This means that gait pattern disorders and a higher risk of falling may occur in patients operated on for the most common malignancies much earlier than indicated by the literature review [39][40][41]. It is recognized that falls are a serious problem among older people; the incidence of falls increases with age [42].…”
Section: Discussionmentioning
confidence: 99%